Wissenschaftliche und wissenschaftspolitische Produktionsweisen im Neoliberalismus.: Beiträge der Mont Pèlerin Society und marktradikaler Think Tanks zur Hegemoniegewinnung und -erhaltung - Plehwe, Dieter; Walpen, Bernhard (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1999)
Employing Gramsci’s concept of hegemony the rise of neoliberalism to the dominant force in the present hegemonic constellation is scrutinized. The origin and development of the Mont Pèlerin Society of right wing liberals around Hayek is traced and the network of think tanks stretching from the British Institute of Economic Affairs to the Heritage Foundation in the U.S. is examined with regard to the working relations of neoliberal discourse coalitions and epistemological communities. The article thus underlines the role ideas play in the struggle to win and to stabilize hegemony in society and stresses the material and organizational basis of the production of powerful ideas. A short discussion of the challenges a new left would have to confront draws lessons from the neoliberal success story.